The legality of online arbitration agreements: whither lays Nigeria? (2015)
The development in technology, especially the Internet, has brought about exponential growth in legal relations cutting across diverse jurisdictions with little or no obstacle. This new method of communication brings people together and it is inevitable that conflicts will ensue. It is a known fact that many cybercitizens enter into online arbitration agreements in case of any dispute. Many countries have developed legal approaches to online arbitration agreements in order to give validity to such agreements. Arbitration is not a new phenomenon in Nigeria which has embedded in its legal system laws regulating such arrangement. However, the issue of online or cyber-arbitration agreement is somewhat new to the arbitration law in Nigeria: thus, this work tends to identify the position, if any, that Nigeria takes on the issue of arbitration agreement entered online, especially in standard form contracts where the terms of such agreement are formulated by one party to a contract.